PENGARUH PERUBAHAN STRUKTUR KELEMBAGAAN DAN GAYA KEPEMIMPINAN TERHADAP DISIPLIN KERJA SERTA DAMPAKNYA TERHADAP KINERJA PEGAWAI KANWIL KEMENKUM SUMATERA SELATAN - Debie Angrainie; Sari Sakarina; Yolanda Veybitha (LPPM Universitas Ibnu Sina, 2025)
This study aims to examine the effect of changes in institutional structure and leadership style on work discipline and the impact of the performance Regional Office Employees at the Ministry of Law, South Sumatra. The population in this study consisted of all 87 employees at the office, and the census method was applied, meaning the entire population was used as the sample. Data analysis was conducted using the Structural Equation Modeling (SEM) approach with Partial Least Squares (PLS) software. The results show that competence significantly institutional structure and leadership style with work discipline and performance. There is competence significantly work discipline and leadership style with employee performance. This study identified indirect effects, where work discipline partially mediates the relationship between institutional structure and leadership style with Employee Performance. The R² value for the latent variable Work Discipline as a mediating variable is 0.654, so it means that this value identifies that variations in Employee Work Discipline can be explained by external latent variables (Institutional Structure and Leadership Style) by 65.4% and then the remaining 34.6% is explained by other variables, and the R² value for the Performance latent variable is 0.872, indicating that 87.2% of the variation in Performance can be explained by external variables (Institutional Structure, Leadership Style, and Work Discipline), while the remaining 12.8% is explained by variables not included in the study. This study recommends that the Head of the South Sumatra Regional Office the Ministry of Law evaluate the changes in institutional structure and leadership style that are relevant, as well as the existing condition of employees, in order to improve and optimize efforts to change the institutional structure, leadership style, and work discipline.